Psychosis Recovery Orientation in Malawi by Improving Services and Engagement (PROMISE) protocol. - Stephen Lawrie; Charlotte Hanlon; Lucinda Manda-Taylor; Martin Knapp; Martyn Pickersgill; Robert C Stewart; Jen Ahrens; Judith Allardyce; Action Amos; Annette Bauer; Erica Breuer; Dennis Chasweka; et al. (PLoS ONE)
Malawi has a population of around 20 million people and is one of the world's most economically deprived nations. Severe mental illness (largely comprising psychoses and severe mood disorders) is managed by a very small number of staff in four tertiary facilities, aided by clinical officers and nurses in general hospitals and clinics. Given these constraints, psychosis is largely undetected and untreated, with a median duration of untreated psychosis (DUP) of around six years. Our aim is to work with people with lived experience (PWLE), caregivers, local communities and health leaders to develop acceptable and sustainable psychosis detection and management systems to increase psychosis awareness, reduce DUP, and to improve the health and lives of people with psychosis in Malawi. We will use the UK Medical Research Council guidance for developing and evaluating complex interventions, including qualitative work to explore diverse perspectives around psychosis detection, management, and outcomes, augmented by co-design with PWLE, and underpinned by a Theory of Change. Planned deliverables include a readily usable management blueprint encompassing education and community supports, with an integrated care pathway that includes Primary Health Centre clinics and District Mental Health Teams. PWLE and caregivers will be closely involved throughout to ensure that the interventions are shaped by the communities concerned. The effect of the interventions will be assessed with a quasi-experimental sequential implementation in three regions, in terms of DUP reduction, symptom remission, functional recovery and PWLE / caregiver impact, with quality of life as the primary outcome. As the study team is focused on long-term impact, we recognise the importance of having embedded, robust evaluation of the programme as a whole. We will therefore evaluate implementation processes and outcomes, and cost-effectiveness, to demonstrate the value of this approach to the Ministry of Health, and to encourage longer-term adoption across Malawi.